2019
DOI: 10.4012/dmj.2018-145
|View full text |Cite
|
Sign up to set email alerts
|

Long-term water sorption and solubility of experimental bioactive composites based on amorphous calcium phosphate and bioactive glass

Abstract: The aim of this study was to evaluate water sorption and solubility of two series of experimental composites containing amorphous calcium phosphate (ACP) or bioactive glass (BG). Water sorption and solubility were measured for up to 287 days. The surface precipitation of calcium phosphates was evaluated by scanning electron microscopy. The ACP-series showed higher water sorption (223-568 µg/mm 3) than the BG-series (40-232 µg/mm 3). In contrast, the ACP-series had generally lower solubility (37-106 µg/mm 3) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
3
18
0
4
Order By: Relevance
“…However, the loss of mass was observed with CN which could be due to the release of soluble species from reactive fillers. The similar result was obtained in the experimental resin composites containing soluble reactive fillers 21,36) .…”
Section: Mass and Volume Changessupporting
confidence: 88%
“…However, the loss of mass was observed with CN which could be due to the release of soluble species from reactive fillers. The similar result was obtained in the experimental resin composites containing soluble reactive fillers 21,36) .…”
Section: Mass and Volume Changessupporting
confidence: 88%
“…The Zn-PBG-containing flowable resin composite can release calcium and phosphate ions to prevent dental caries, and the silica glass filler provides the required load-bearing ability. Previous studies have investigated the remineralization of demineralized teeth using composite materials that release calcium and phosphate ions, such as composites containing hydroxyapatite, α-tricalcium phosphate, B-tricalcium phosphate, and 45S5 bioactive glass as fillers [25,27,28]. These studies revealed that the bioactive glass in the composite resin has bioactive properties and leads to the formation of tooth-like hydroxyapatite [29].…”
Section: Discussionmentioning
confidence: 99%
“…Although considerable stress reductions were observed in the C-series by using BG amounts of 40–60 wt%, such high fractions of unsilanized versus reinforcing fillers would considerably diminish mechanical properties, especially since higher BG amounts also led to reduced DC 47 . The mechanical properties could be expected to further decrease over time due to high water sorption caused by soluble BG fillers 48 .…”
Section: Discussionmentioning
confidence: 99%